Effect of Black Pointed Seed and Vermicompost on Leaf and Seed Infection of Wheat caused by Bipolaris sorokiniana - Islam, M. N.; Chowdhury, S. R.; Aminuzzaman, F. M.; Saha, S.; Mahato, A. K. (International Journal of Bio-resource and Stress Management, 2019)
An experiment was conducted to find out the effect of different levels of black pointed seed and vermicompost in soil on leaf blight (Bipolaris sorokiniana) severity, yield attributes and seed health status of harvested seed of wheat, cv. Shatabdi. In the field experiment in RCBD design with 18 treatments, the maximum (114.3 and 124.0) emergence of seedling was recorded from apparently healthy seed treated with Provax 200 @ 0.25% sown in soil amended with vermicompost @ 1.5 t ha-1 after 7 days and 15 days of sowing, respectively. Leaf blight severity (0-5 scale) on flag leaf and penultimate leaf in flag leaf stage, panicle initiation stage, flowering stage, milking stage and hard dough stage were recorded the maximum when 25% black pointed seeds in weight basis were sown without vermicompost. The treatments showed significant variations on number of grains per ear of different severity grades (0-5). Significantly higher 1000 seeds weight (42.70g), grain yield (3.66 t ha-1) and straw yield (4.33 t ha-1) were recorded from the plants germinated from apparently healthy seed treated with Provax 200 @ 0.25% sown in soil with of vermicompost @ 1.5 t ha-1. In laboratory experiments, decreasing trend of germination, normal seedling percentage, shoot length, root length, seedling weight and vigor index (VI) of the seedlings emerged from increasing levels of black pointed seed sown revealed that apparently healthy seed treated with Provax 200 @ 0.25% sown with vermicompost @ 1.5 t ha-1 and showed promising results in respect of disease severity on leaf and quality seed production.